2021
DOI: 10.1111/tbj.14174
|View full text |Cite
|
Sign up to set email alerts
|

Reducing time to treatment and patient costs with breast cancer: the impact of patient visits

Abstract: Background The purpose of this study was to evaluate the impact of processes aimed at reducing time to treatment initiation (TTI) on minimizing the days spent to complete pretreatment visits and the associated costs for patients with nonmetastatic breast cancer. Methods System‐wide initiatives were implemented in 2014 to minimize TTI, by incorporating multiple strategies (eg, creation of teams, patient liaisons, process mapping) and enhanced communication to increase coordinated visits. Average number of days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Of our 53 included studies, 15 (28%) reported person-level procedure costs [ 20 , 27 , 28 , 32 , 34 , 35 , 46 , 47 , 49 , 51 , 60 , 63 , 64 , 69 , 71 ]; 19 (36%) reported person-level costs over a 1-year time horizon [ 19 , 23 , 25 , 26 , 29 , 33 , 38 40 , 43 , 45 , 48 , 50 , 52 , 56 59 , 65 ]. As such, the costs from 34 (64%) studies per person for procedures and then over a 1-year time frame are presented in Table 3 and 4 , respectively, with the other included studies’ costs presented in Supplementary Excel Sheet 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of our 53 included studies, 15 (28%) reported person-level procedure costs [ 20 , 27 , 28 , 32 , 34 , 35 , 46 , 47 , 49 , 51 , 60 , 63 , 64 , 69 , 71 ]; 19 (36%) reported person-level costs over a 1-year time horizon [ 19 , 23 , 25 , 26 , 29 , 33 , 38 40 , 43 , 45 , 48 , 50 , 52 , 56 59 , 65 ]. As such, the costs from 34 (64%) studies per person for procedures and then over a 1-year time frame are presented in Table 3 and 4 , respectively, with the other included studies’ costs presented in Supplementary Excel Sheet 1.…”
Section: Resultsmentioning
confidence: 99%
“…Nine (17%) studies reported indirect costs [ 34 , 43 , 54 57 , 59 61 ]. Productivity loss is a key indirect cost for consideration, often estimated via the human capital approach, i.e., take the patient’s perspective and count any hour not worked as an hour lost, or the friction cost approach, i.e., take the employer’s perspective and only count lost hours not worked until another employee takes over the patient’s work [ 72 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with previous studies in Mexico and Latin America, lack of infrastructure, insufficient human resources, and saturated health services were identified as major barriers to care [21][22][23] . Identifying these barriers has allowed the development of different strategies aimed at reducing delays in care 16,17,[24][25][26][27][28][29][30][31][32] . Among these initiatives, we highlight the development of national guidelines, the creation of rapid reference pathways for patients with symptoms suggestive of BC, the implementation of patient navigation programs, and the adoption of telemedicine 16,17,[24][25][26][27][28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Identifying these barriers has allowed the development of different strategies aimed at reducing delays in care 16,17,[24][25][26][27][28][29][30][31][32] . Among these initiatives, we highlight the development of national guidelines, the creation of rapid reference pathways for patients with symptoms suggestive of BC, the implementation of patient navigation programs, and the adoption of telemedicine 16,17,[24][25][26][27][28][29][30][31][32] . Particularly in Mexico, the Alerta Rosa program was created as a strategy to improve patient navigation and prioritization 27,28 .…”
Section: Discussionmentioning
confidence: 99%